ChemInform Abstract: Synthesis of Dibenzoxanthene and Acridine Derivatives Catalyzed by 1, 3‐Disulfonic Acid Imidazolium Carboxylate Ionic Liquids. Issue 12 (March 2015) - Dutta, Arup Kumar; Gogoi, Pinky; Borah, Ruli
Abstract The acidity order of the new applied ionic liquid in Hammet plot corresponds to its catalytic activity.